From the research of economic motivation and metrological behaviour of economic entities to the research of metrological systems in economics as a specific type of systems - Bashnyanyn, G. I. (Publishing House of Lviv Polytechnic National University, 2015)
The basic historical types of economic motivation of economic entities as fundamentals of forming both the main historical types of metrological behavior and the most fundamental types of economic measurement are defined. A general characteristic of nominal, real and super-real economic measurements as the main subject of an economic metrology being a general theory of economic measurement is given. Based on the previous definition of the basic types of economic measurement a general characteristic of appropriate metrological systems in economics, namely, nominal, real and super-real ones is offered.
Keywords: economic motivation; metrological behavior; economic measurement; nominal; real and super-real economic measurement; metrological systems; nominal; real and super-real metrological systems; economic metrology; metrological economy